Revision of the South American Ninetinae genus Guaranita (Araneae, Pholcidae) - Bernhard A. Huber; Guanliang Meng; Jiří Král; Ivalú M. Ávila Herrera; Matías A. Izquierdo (European Journal of Taxonomy, 2023)
The southern South American genus Guaranita includes tiny spiders (body length ~1 mm) that lead reclusive lives under ground-objects and run rapidly when disturbed. As a result, they have been poorly collected and studied. Here we report on a recent collection of Guaranita spiders from Argentina, describing one new species (G. auadae Huber sp. nov.) and the previously unknown female of G. dobby Torres et al., 2016. In addition, we provide CO1 barcodes for all (now five) known species, first SEM data, and first chromosome data for the genus. The diploid number of Guaranita goloboffi Huber, 2000 (2n♂ = 11) is among the lowest in araneomorph spiders with monocentric chromosome structure.